Phytomedicine in Disease Management: In-Silico Analysis of the Binding Affinity of Artesunate and Azadirachtin for Malaria Treatment - Okoh, Michael P.; Singla, Rajeev K.; Madu, Chijioke; Soremekun, Opeyemi; Adejoh, Johnson; Alli, Lukman A.; Shen, Bairong (Frontiers in Pharmacology, 2021)
In sub-Saharan African (sSA) countries, malaria is managed in rural communities using phytocompounds. Here, we, using recent scientific advances to understand the complex life cycle of mosquito malaria transmission; their involvement in cerebral malaria via synaptic binding simulation and relate this with phytochemical properties of the plant (Neem), to reduce malaria scourge. With molecular dynamics (MD), binding free energy estimations, comparing the binding affinity of artesunate and azadirachtin to Gephyrin E was done. MD simulation gave insights to structural changes upon binding of artesunate and azadirachtin in the ligand-binding pocket of Gephyrin E. Root mean square deviation (RMSD) and root mean square fluctuation (RMSF) were calculated. From the estimation, azadirachtin had a total binding energy of -36.97kcal/mol; artesunate a binding energy of -35.73kcal/mol. The GRIP docking results, provided a clearer evidence that artesunate has comparatively more binding affinities to Gephyrin E than azadirachtin, and the critical binding sites (in activity order) were cavity 3, 2, 8, and 6 for artesunate while for azadirachtin, it was cavity 6, 3, 8, and 2. Constituent interactions for both molecules with 6FGC amino acid residues were analysed and compared. The GRIP docking provided detailed interactions at the atomic levels, providing evidence; both compounds have chances to overcome the drug resistance problem, albeit, higher for artesunate. Our findings suggest, azadirachtin properly developed may be effective as an anti-malarial agent. The combination of disparate molecular/biophysical tools for insights into natural bioactive compounds useful for rational drug design, are essential in the race to manage all forms and stages of malaria. This is even more imperative as there remains dearth of literature on risk factors for cognitive impairment due to cerebral malaria. The results herein, may provide, impetus for more studies into bioactive components of plant origin towards the effective management of malaria disease phenotype.